THE ROLE AND THE IMPORTANCE OF IDIOMATIC EXPRESSIONS IN ENGLISH LANGUAGE (Ustozlar uchun, 2026)
Idiomatic expressions represent one of the most expressive and culturally rich layers of the English language. They function as fixed or semi-fixed combinations of words whose meanings are often figurative and cannot be fully interpreted through a literal analysis of their components. This thesis explores the role and importance of idiomatic expressions in English from linguistic, cognitive, pragmatic, and cultural perspectives. Idioms play a crucial role in shaping natural communication, enabling speakers to convey complex ideas, emotions, and evaluations in a concise and vivid manner. The study examines the semantic characteristics of idioms, their cognitive motivation through metaphorical thinking, and their pragmatic functions in discourse. Particular attention is given to the role of idiomatic expressions in spoken interaction, literary and media discourse, and professional communication. The thesis also addresses the challenges idioms pose for learners of English as a second or foreign language and emphasizes idiomatic competence as a key indicator of advanced proficiency and native-like fluency. By highlighting the multifunctional nature of idiomatic expressions, this research underscores their central importance in enriching the expressive potential, cultural depth, and communicative effectiveness of the English language.